Emergent neutrality or hidden niches?. Issue 11 (27th August 2013) - Barabás, György; D'Andrea, Rafael; Rael, Rosalyn; Meszéna, Géza; Ostling, Annette
Abstract : Emergent neutrality is the idea in community ecology that species interactions may drive a system in a direction where some species become so similar that this similarity will be the primary cause for their coexistence instead of niche differentiation. A recent, widely cited model of emergent neutrality is by Scheffer and van Nes, later applied to species abundance distribution patterns by Vergnon et al. We take issue with the ecological interpretation of this model, demonstrating that it in fact presupposes important differences between superficially similar‐looking species. We argue that the temptation to interpret the model as one of emergent neutrality stems from the fact that these differences are unmodeled and therefore hidden, obscuring the underlying coexistence mechanisms. We therefore claim that the model is actually one of hidden niches, and present several alternative ways to make its hidden portions more explicit. These alterations to the model also make its proper interpretation as one of hidden niches more transparent. We also polemize with the claim of Vergnon et al. that multimodality in species abundance distributions is support for their emergent neutrality model: we demonstrate that appropriate stochastic versions of classical resource partitioning or even neutral models can lead to such patterns in a robust way. Observation of these patterns is therefore inconclusive as to the underlying mechanisms that generate them.